2021
DOI: 10.1155/2021/8159879
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes in Tuberculosis via Bioinformatics Analysis

Abstract: Background. Tuberculosis (TB) is a serious chronic bacterial infection caused by Mycobacterium tuberculosis (MTB). It is one of the deadliest diseases in the world and a heavy burden for people all over the world. However, the hub genes involved in the host response remain largely unclear. Methods. The data set GSE11199 was studied to clarify the potential gene network and signal transduction pathway in TB. The subjects were divided into latent tuberculosis and pulmonary tuberculosis, and the distribution of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…KEGG enrichment results showed that DEGs stimulated by Mtb-Ag are mainly related to cytokine-cytokine receptor interactions, the JAK-STAT signaling pathway, the TNF signaling pathway, the IL-17 signaling pathway, the NF-κB signaling pathway, and the C-type lectin receptor signaling pathway. These pathways are closely related to tuberculosis’s pathogenesis ( Turrin and Plata-Salamán, 2000 ; Rawlings et al., 2004 ; Wu et al., 2021 ; Zhang T et al., 2021 ). This suggests that GO and KEGG were practical ways to further investigate the mechanism of action of Mtb-Ag in tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment results showed that DEGs stimulated by Mtb-Ag are mainly related to cytokine-cytokine receptor interactions, the JAK-STAT signaling pathway, the TNF signaling pathway, the IL-17 signaling pathway, the NF-κB signaling pathway, and the C-type lectin receptor signaling pathway. These pathways are closely related to tuberculosis’s pathogenesis ( Turrin and Plata-Salamán, 2000 ; Rawlings et al., 2004 ; Wu et al., 2021 ; Zhang T et al., 2021 ). This suggests that GO and KEGG were practical ways to further investigate the mechanism of action of Mtb-Ag in tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other hub-central gene of the brown module, including CSF1 ( Chatterjee et al, 2021 ), PLAUR ( McLoughlin et al, 2021b ), ITGB1 ( Yang et al, 2017 ), CCND1 ( Koo et al, 2012 ; Looney et al, 2021 ), CSF2 ( Marsay et al, 2013 ; Shukla et al, 2017 ; Abdelaal et al, 2022 ), CTLA4 ( Zhang et al, 2021 ), FLNA ( Xu et al, 2015 ), CCND2 ( Lavalett et al, 2017 ), WEE1 ( Jayaswal et al, 2010 ), MMP9 ( Blanco et al, 2012 ; McLoughlin et al, 2014 ), CDC25A ( Shapira et al, 2020 ), CSF2RB ( Benmerzoug et al, 2018 ), TIMP1 ( Sun et al, 2020 ), CD69 ( Li et al, 2011 ; Chen et al, 2020 ), PTPN22 ( Boechat et al, 2013 ), CD38 ( Silveira-Mattos et al, 2019 ), IL7R ( Jenum et al, 2016 ; Alsulaimany et al, 2022 ), IL1RN ( Alcaraz-López et al, 2020 ), and IDO1 ( Weiner et al, 2012 ; Gautam et al, 2018 ) were also involved in host-pathogen interactions as well as suppression of host immune response. For example, the CTLA4 hub-central gene encodes an inhibitor of T cell-mediated response ( Schneider et al, 2006 ), and the upregulation of this gene in response to M. bovis infection may reflect a mechanism of immunomodulation used by M. bovis to subvert a host T-cell response ( Killick et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…We additionally applied gene/protein enrichment and network analysis to the set of the above six mutated genes by making use of the STRING tool. This kind of analysis was shown to be useful in recent studies aimed to decipher the emergence of drug resistance, and to elucidate the potential gene network and signaling pathways in pulmonary TB through gene/protein network analysis [22][23][24].…”
Section: Gene/protein Enrichment and Network Analysismentioning
confidence: 99%